Optimal power allocation and allowable interference shaping in cognitive radio networks. (October 2018) - Lee, Hyang-Won; Chang, Woohyuk; Jung, Bang Chul
Abstract: We investigate an interference management problem in multi-carrier cognitive radio systems. To this end, we propose a new framework for protecting primary users such that the primary user can shape the envelope of interference on each subcarrier. Furthermore, we introduce the concept of minimum individual interference budget that the primary user should allow on each subcarrier so that the secondary user can receive a certain quality of service. We develop a joint optimal transmit power and interference budget allocation algorithm for the primary user, which maximizes the throughput of the primary user. Through simulations, we show that our approach can provide better protection for primary users than the existing approach.